Old English poetry, verse by verse. (18th November 2016) - Weiskott, Eric
Abstract: Certain syntactical ambiguities in Old English poetry have been the focus of debate among students of metre and syntax. Proponents of intentional ambiguity must demonstrate that the passages in question exhibit, not an absence of syntactical clarity, but a presence of syntactical ambiguity. This article attempts such a demonstration. It does so by shifting the terms of the debate, from clauses to verses and from a spatial to a temporal understanding of syntax. The article proposes a new interpretation of many problematic passages that opens onto a new way of parsing and punctuating Old English poetry. In this essay in the history of poetic style, I demonstrate that the sequence in time of Old English half-lines sometimes necessitates retrospective syntactical reanalysis, a state of affairs which modern punctuation is ill-equipped to capture, but in which Anglo-Saxon readers and listeners would have recognized specific literary effects. In the second section, I extrapolate two larger syntactical units, the half-line sequence and the verse paragraph, which differ in important ways from the clauses and sentences that modern editors impose on Old English poetic texts. Along the way, I improve the descriptive accuracy of Kuhn's Laws by reinterpreting them as governing half-line sequences rather than clauses. I conclude with a call for unpunctuated or minimally punctuated critical editions of Old English verse texts.